Cyrille de Jérusalem: Homélie sur la Présentation de Jésus - Beylot, Robert (Aethiopica, 2007)
A greek homily for the Presentation of the Lord is kept, attributed to Cyril from Jerusalem. This composition is also known in coptic and arabic language. It is now considered as apocryphal. The unpublished ethiopic version of this text is found in three mss, the oldest of them is from the fourteenth century.